1999
DOI: 10.1203/00006450-199908000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Characterization of Hematopoietic Progenitor Cells from Fetal Bone Marrow, Adult Bone Marrow, Peripheral Blood, and Cord Blood

Abstract: Hematopoietic stem cell transplantation has been increasingly used to replace a defective hematopoietic system and to treat various genetic defects as well as malignant diseases. However, the limitations of conventional bone marrow transplantation have stimulated an intense interest in exploring the use of alternative sources of hematopoietic stem cells, including peripheral blood mononuclear cells (PBMC) and cord blood (CB). A major investigative effort of our laboratory has been focused on evaluating fetal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 33 publications
2
19
1
Order By: Relevance
“…Hematopoietic stem cells seem to display ontogenetic age-dependent differences in growth properties. For example, there is a notably decreased clonogenic potential and proliferative responsiveness in mixed lymphocyte reaction assays observed in adult hematopoietic stem cells as compared with stem cells isolated from fetal bone marrow (19). Because proliferating cells express higher levels of DNA topoisomerase II as compared with quiescent cells (20), a fetus, who has periods of rapid cell turnover, may be more susceptible than an adult to the effect of dietary DNA topoisomerase II inhibitors.…”
mentioning
confidence: 99%
“…Hematopoietic stem cells seem to display ontogenetic age-dependent differences in growth properties. For example, there is a notably decreased clonogenic potential and proliferative responsiveness in mixed lymphocyte reaction assays observed in adult hematopoietic stem cells as compared with stem cells isolated from fetal bone marrow (19). Because proliferating cells express higher levels of DNA topoisomerase II as compared with quiescent cells (20), a fetus, who has periods of rapid cell turnover, may be more susceptible than an adult to the effect of dietary DNA topoisomerase II inhibitors.…”
mentioning
confidence: 99%
“…1). These data were obtained from a flow cytometric analysis [26]. The same analysis showed that the FBM cells contained a very low population of cells that expressed the CD3 and CD16 markers, indicating that FBM is least predisposed to induce graft-versus-host disease.…”
Section: Comparative Study Of Stem Cells Derived From Various Sourcesmentioning
confidence: 99%
“…In our earlier work, we demonstrated that FBM has distinctive biological and therapeutic properties, ideal for transplantation. Further, successful engraftment and cellular reconstitution of these cells demonstrated compelling evidence for a higher replicative cell potential of the more imma- ture source of stem cells [24][25][26]. We tested the functional efficacy of FBM from lost pregnancies in these studies, with the goal of determining the best sources of cells for transplantation.…”
Section: Comparative Study Of Stem Cells Derived From Various Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…+ -expressing cells (6,7). It is not known whether CD34 + cells (defined by HUCBC lymphocytes and monocytes that contained over 95% CD34 + -expressing cells) can be used as a prophylactic agent for experimental heatstroke.…”
Section: Introductionmentioning
confidence: 99%